Deficit irrigation and sustainable water-resource strategies in agriculture for China's food security. (3rd April 2015) - Du, Taisheng; Kang, Shaozhong; Zhang, Jianhua; Davies, William J.
Highlight: This review summarizes the extent of use and impact of deficit irrigation within China and proposes a sustainable strategy for allocation of agricultural water resources for food security. Abstract : More than 70% of fresh water is used in agriculture in many parts of the world, but competition for domestic and industrial water use is intense. For future global food security, water use in agriculture must become sustainable. Agricultural water-use efficiency and water productivity can be improved at different points from the stomatal to the regional scale. A promising approach is the use of deficit irrigation, which can both save water and induce plant physiological regulations such as stomatal opening and reproductive and vegetative growth. At the scales of the irrigation district, the catchment, and the region, there can be many other components to a sustainable water-resources strategy. There is much interest in whether crop water use can be regulated as a function of understanding of physiological responses. If this is the case, then agricultural water resources can be reallocated to the benefit of the broader community. We summarize the extent of use and impact of deficit irrigation within China. A sustainable strategy for allocation of agricultural water resources for food security is proposed. Our intention is to build an integrative system to control crop water use during different cropping stages and actively regulate the plant's growth, productivity, and development based on physiological responses. This is done with a view to improving the allocation of limited agricultural water resources.